Spatial Disparity of Knowledge Levels on Reproductive Health among Indonesia’s Adolescents: Spatial Analysis of 2017 IDHS Data - Muhammad Rafif; Umi Listyaningsih (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
The high number and percentage of Indonesia’s adolescent population cannot be separated from the problems related to adolescent reproductive health, especially the lack of knowledge about reproductive health among Indonesia’s adolescents in. This study aims to analyze the spatial distribution of knowledge on adolescent reproductive health in Indonesia. This study is a quantitative study using secondary data of 2017 IDHS data. Adolescent reproductive health knowledge is measured in a composite index by taking into account the five indicators, including knowledge of signs of puberty, fertile period and risk of pregnancy, anemia, HIV/ AIDS, and other sexually transmitted infections. This study used a comparative spatial analysis. The results confirmed that there were differences in the spatial distribution of the adolescents’ knowledge level related to reproductive health in each province based on the adolescents’ characteristics, including sex, age, and education level.